Status and Dynamics of Forests in Germany Results of the National Forest Monitoring - Wellbrock, Nicole; Bolte, Andreas (Ecological Studies, Analysis and Synthesis,, 2019)
This book is an open access publication. Forest ecosystems in Central Europe are changing as a result of anthropogenic influences and changing climate conditions. As such, a large-scale monitoring programme was undertaken in order to understand the influence of site modification, deposition of air pollutants, and climate. This book presents the scientific findings of this study for Germany, including the major challenges with regard to the future preservation and management of forest ecosystems under environmental change. In addition, it addresses a number of central questions: what are the main factors affecting forest stands and soil integrity? How, and how rapidly, are forest ecosystems changing? How diverse are the changes across Germany? What will be the main risks in sustainable forest management in the future? And how can policy support the development and maintenance of adaptive and resilient forests that provide essential ecosystem services, today and in the future? Helping readers understand the importance of soils and related ecosystem processes for future sustainable forestry, and sharing essential findings on environmental change and related changes in forest status and dynamics, the book is a valuable resource for researchers and policymakers interested in science-based decisions.